2017
DOI: 10.1016/j.ergon.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material elastic properties and surface roughness on grip performances of ski boot soles under wet and icy conditions

Abstract: A set of thermoplastic materials employed in soles for alpine skiing boots were characterized in terms of chemical composition, cristallinity, hardness, surface roughness, and grip. The results of friction experiments on different substrates reproducing the real environmental scenarios point out that materials provide more grip as they become softer. Moreover, higher roughness results in lower dynamic coefficient of friction (COF). Finite element simulations corroborate the experimental measures of COF and let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Besides, it was aimed to grip the object with minimum energy, [7]. The experiments showed that, when materials became softer, there were a very high grasp of objects according to the friction results between different objects and when the dynamic of friction coefficient became lower, the results of roughness showed higher trend, [8]. The suggested flexible universal gripper is an inexpensive and comprehensive solution to handle objects of variable shape.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was aimed to grip the object with minimum energy, [7]. The experiments showed that, when materials became softer, there were a very high grasp of objects according to the friction results between different objects and when the dynamic of friction coefficient became lower, the results of roughness showed higher trend, [8]. The suggested flexible universal gripper is an inexpensive and comprehensive solution to handle objects of variable shape.…”
Section: Introductionmentioning
confidence: 99%